Diagnosis and classification of personality disorders: novel approaches. Issue 1 (January 2019) - Mulder, Roger; Tyrer, Peter
Abstract : Purpose of review: To provide an update of the recent studies, which have evaluated the radical changes in personality disorder classification in DSM-5 and ICD-11 . Recent findings: Although the DSM-5 Committee rejected the personality disorders Work Group proposal for personality disorder classification, the model was published in DSM-5 Section III. This Alternative Model of Personality Disorders (AMPD) has been widely adopted by the research community resulting in multiple studies evaluating its reliability and clinical utility. The ICD-11 Personality Classification has recently been accepted by the WHO and is also receiving increasing study. Both models emphasize personality disorder severity, which most studies report is consistently linked to impairment and outcome. Both models propose five descriptive domains, which appear to capture most of the current personality disorder diagnoses, and can also be linked to disease extremes of normal personality such as the Five Factor Model. Summary: The changes in DSM-5 AMPD and ICD-11 represent a significant paradigm shift in the diagnosis of personality disorders. Early research suggests that the changes may be beneficial for clinicians and researchers. The models more closely align with the large body of literature supporting dimensional models of normal personality. The severity dimensions are consistent with the large body of evidence that personality disorder severity is a strong determinant of impairment and outcome. It remains to be seen if clinicians will use the classification to plan and predict treatment for a wide range of mental disorders.